"When are We Ever Going to Have to Use This?": Discussing Programmatic Learning Outcomes in the Classroom. Issue 4 (2nd October 2019) - Safronova, Margarita; Miller, Caleb; Kuehl, Colin
Abstract: How can professors more effectively persuade students to care about political science? The use of different metacognitive strategies, in which the student actively reflects on the learning process, helps students become more engaged by pushing them to critically consider the value in what they are doing. In this article, we explore one possible means of prompting student metacognitive thinking process: explicitly emphasizing programmatic learning outcomes (PLOs) in the classroom to signal the external value of the skills the students gain in political science. Specifically, we employ a quasi-experimental design to explore the effects of emphasizing course PLOs on student metacognition by measuring the student's perception of a course's overall utility, their sense of whether the skills learned in the course can be used in future academic and professional endeavors. The results show that the discussion of PLOs has a positive and statistically significant effect on the students' metacognition score, suggesting that instructors ought to make greater efforts to discuss the PLOs associated with a given course.